2023
DOI: 10.1080/13416979.2023.2232086
|View full text |Cite
|
Sign up to set email alerts
|

Forest bathing diminishes anxiety in undergraduate students: a pilot study in the Valdivian temperate rainforest

Álvaro I. Langer,
Esteban Solano,
Leonardo D. Bacigalupe
et al.

Abstract: Table S1. Candidate models to evaluate the impact of intervention treatment (i.e. Treatment; city versus forest), time (i.e. Time; pre-intervention versus port-intervention), intervention treatment plus time (i.e. Additive) and intervention treatment in interaction with time (i.e. Interaction), on one physiological (MAP) and five psychological variables (see Methods for further details). K: number of parameters; AICc: AIC values corrected for small sample sizes, ΔAICc: delta AICc between each model and the one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The focus of forest therapy interventions in eight studies was stress reduction, with measurements taken for systolic blood pressure (SBP) and diastolic blood pressure (DBP). In two studies [34,50], no changes in the participants' SBP and DBP before and after the intervention were observed. The authors of one study [50] posited that the recruited university student population had good blood pressure levels before the experiment, while the authors of the other study suggested that the lack of change in the participants' blood pressure was due to the short duration of forest bathing (only 15 min), which was insufficient to induce physiological changes.…”
Section: Cardiovascular Outcomesmentioning
confidence: 92%
See 4 more Smart Citations
“…The focus of forest therapy interventions in eight studies was stress reduction, with measurements taken for systolic blood pressure (SBP) and diastolic blood pressure (DBP). In two studies [34,50], no changes in the participants' SBP and DBP before and after the intervention were observed. The authors of one study [50] posited that the recruited university student population had good blood pressure levels before the experiment, while the authors of the other study suggested that the lack of change in the participants' blood pressure was due to the short duration of forest bathing (only 15 min), which was insufficient to induce physiological changes.…”
Section: Cardiovascular Outcomesmentioning
confidence: 92%
“…In two studies [34,50], no changes in the participants' SBP and DBP before and after the intervention were observed. The authors of one study [50] posited that the recruited university student population had good blood pressure levels before the experiment, while the authors of the other study suggested that the lack of change in the participants' blood pressure was due to the short duration of forest bathing (only 15 min), which was insufficient to induce physiological changes. In seven studies, the participants exhibited significant decreases in both SBP and DBP, with one study finding this effect sustained for up to 5 days [36].…”
Section: Cardiovascular Outcomesmentioning
confidence: 92%
See 3 more Smart Citations